2015
DOI: 10.1038/ncomms10155
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disturbed peatlands on river outgassing in Southeast Asia

Abstract: River outgassing has proven to be an integral part of the carbon cycle. In Southeast Asia, river outgassing quantities are uncertain due to lack of measured data. Here we investigate six rivers in Indonesia and Malaysia, during five expeditions. CO2 fluxes from Southeast Asian rivers amount to 66.9±15.7 Tg C per year, of which Indonesia releases 53.9±12.4 Tg C per year. Malaysian rivers emit 6.2±1.6 Tg C per year. These moderate values show that Southeast Asia is not the river outgassing hotspot as would be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(120 citation statements)
references
References 41 publications
9
106
3
2
Order By: Relevance
“…However, as indicated in experiment 1, such a low DOC groundwater concentration can only explain the DOC end-member concentration measured during our last expedition in April 2013 if one assumes an evapotranspiration of 67.7% as observed in pristine peat swamps ( Figure 3A). Considering however the overall status of Sumatran peat lands this appears unlikely which in turn supports the hitherto held assertion that an enhanced DOC respiration associated with the occurrence of a plankton bloom lowered the DOC concentrations in the Siak estuary in April 2013 (Wit et al, 2015).…”
Section: Numerical Leaching Experiments For the Siakmentioning
confidence: 53%
See 1 more Smart Citation
“…However, as indicated in experiment 1, such a low DOC groundwater concentration can only explain the DOC end-member concentration measured during our last expedition in April 2013 if one assumes an evapotranspiration of 67.7% as observed in pristine peat swamps ( Figure 3A). Considering however the overall status of Sumatran peat lands this appears unlikely which in turn supports the hitherto held assertion that an enhanced DOC respiration associated with the occurrence of a plankton bloom lowered the DOC concentrations in the Siak estuary in April 2013 (Wit et al, 2015).…”
Section: Numerical Leaching Experiments For the Siakmentioning
confidence: 53%
“…Although this value is within the range of DOC end-member concentrations determined in the other studied rivers ( Table 1) it represents a real exception for the Siak. The low DOC concentrations in the Siak estuary which finally lead to the low DOC endmember concentrations were assumed to be caused by enhanced DOC respiration within an senescent plankton bloom that occurred in the estuary during our expedition (Wit et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed study on rivers draining disturbed peatland areas in Indonesia and Malaysia revealed pCO2 values in the low-salinity areas between 4000 and > 8000 atm. Despite these relatively high pCO2 values, the rates of CO2 outgassing were found to be lower than what global models have generally suggested, implying that local-scale processes and sources of C need to be better constrained to improve region-specific C budgets (Wit et al, 2015).…”
Section: 1mentioning
confidence: 75%
“…An important factor affecting the riverine C fluxes in Southeast Asia is the rapid land use change including deforestation and associated peatland drainage, which can enhance C mobilization from the coastal peatlands and organic rich soils in the 140 region (Baum et al, 2007;Wit et al, 2015). A detailed study on rivers draining disturbed peatland areas in Indonesia and Malaysia revealed pCO2 values in the low-salinity areas between 4000 and > 8000 atm.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation